The cost of cybercrime. (October 2015) - Unknown
Abstract : The annual 'Cost of Cybercrime Study: UK' report by the Ponemon Institute, funded by HP Enterprise Security, says that cybercrime cost UK firms an average of £4.1m in the past year, up from £3.6m the year before.